Hepatitis E Infection in Solid Organ Transplant Recipients in Turkey - Seval Öğüt; Ayça Arzu Sayıner; Barış Otlu; Gülendam Bozdayı; Ayşın Zeytinoğlu; Sebahat Aksaray; Dilek Çolak; Selma Gökahmetoğlu; Murat Aysın (Turkish Journal of Gastroenterology, 2022)
Background: Hepatitis E virus is a re-emerging pathogen with an increase in human cases that can lead to chronic infection in immunosuppressed patients. Turkey is located between Asia and Europe, 2 regions with distinct epidemiological and clinical features of hepatitis E virus infection. This multicenter cross-sectional study aimed to investigate the prevalence of hepatitis E virus infection in liver and kidney transplant recipients in Turkey and to determine the role of possible transmission factors. Methods: A total of 485 plasma samples of solid organ recipients were collected from 7 transplantation centers in Turkey. Samples were tested for anti-hepatitis E virus immunoglobin M, immunoglobin G, and hepatitis E virus ribonucleic acid. Water- and food-related risk factors were evaluated by a questionnaire. Results: Samples of 300 kidney and 185 liver recipients were collected. Hepatitis E virus ribonucleic acid was tested in 472 samples and none were positive. Anti-hepatitis E virus immunoglobin G and immunoglobin M were detected in 84 (17.3%) and 3 (0.6%) patients, respectively. Seropositivity was associated with older age, male gender, being a liver recipient, and being infected with hepatitis B virus and/or hepatitis C virus. None of the patients under the age of 30 were seropositive. Hepatitis E virus immunoglobin G prevalence was higher in the Central East and Southeast Anatolia. Eating raw meat was the only independent variable associated with hepatitis E virus seropositivity. Conclusion: This is the first prevalence study of hepatitis E virus infection in solid organ recipients in Turkey. Anti-hepatitis E virus immunoglobin G prevalence was 17.3% which was higher than the previously reported rate in blood donors. Seropositivity was significantly higher in liver recipients. Despite the high antibody prevalence, none of the patients were viremic. Cite this article as: Öğüt S, Sayıner AA, Otlu B, et al. Hepatitis E infection in solid organ transplant recipients in Turkey. Turk J Gastroenterol. 2022; 33(1): 68-73.